The influence of an animal's social significance on veterinary antimicrobial use–A hierarchy of care - Olmos Antillón, Gabriela; Blanco-Penedo, Isabel; Albernaz-Gonçalves, Rita; Hockenhull, Jo; Hötzel, Maria José (Frontiers in Veterinary Science, 2025)
Antimicrobial resistance (AMR) is a pressing global challenge, and veterinary antimicrobial use is a central focus of regulatory and professional scrutiny. While international policy increasingly requires detailed reporting of veterinary AMU, the social dynamics shaping how and why antimicrobials are prescribed, used, and followed up remain poorly understood. This study applies Social Practice Theory, to explore how AMU is enacted across two contrasting species (dairy cattle and dogs) in three countries with differing AMU profiles: Brazil, Spain, and Sweden. The analysis combined policy and guideline review with 187 semi-structured interviews with veterinary specialists, clinicians, farmers, veterinary students, and dog tutors. Interviews examined how common health problems are observed, diagnosed, treated, and followed up, and how participants defined “optimal antimicrobial use” in their contexts. Our reflexive thematic analysis identified five interconnected themes: (1) species-based hierarchies of care, where the perceived value of animals structured AMU tolerance and diagnostic rigor; (2) imagined animal needs, shaped by assumptions of caretaker expectations or legal boundaries; (3) blurred professional roles, with diagnosis and treatment often shared among farmers, technicians, and suppliers; (4) fragile follow-up practices, where “no news” was commonly taken as treatment success and monitoring systems reduced stewardship to counting doses; and (5) entrenched treatment-first logics, in which antimicrobials became the default response, reinforced by professional habits, regulatory scripts, and cultural valuation of animals. This study highlights the importance of recognizing how animals‘ social significance underpins veterinary practices and AMU decisions. Integrating social theory with ethical considerations provides a more nuanced understanding of veterinary practice and antimicrobial stewardship. By foregrounding species-based hierarchies of care, the research demonstrates how animals' social meanings shape antimicrobial decisions, with implications for animal welfare and public health.